Students' Attitudes Towards Implementation of Hawgent Dynamic Mathematics Software on Curved Surface - Yongxing Huang; Jianlan Tang; Jerito Pereira; Chen Jihe; Maximus Tamur; Hermita Neni (Jurnal Inovasi Matematika, 2021)
Along with the development of the world of science, it is getting faster ICT in education. The objectives to be achieved in this study are to find out how the student's response to the utilization of the Hawgent Dynamic Mathematics application on the material of the curved side of the learning room in the teaching and learning process took place in the classroom. The main object in this study was the 9th-grade junior high school student who was 96 students at Gusui Middle School in Guangxi Zhuang Autonomous Region. Data collection in this study was a questionnaire containing indicators that have to measure the student's response to the use of learning media using Hawgent Dynamic Mathematics and the primary tool processing research data, namely Ms. Excel and SPSS statistical. The study results were related to the student's response that students agreed, were happy, and were assisted by the Hawgent Dynamic application. The perception or student response results concluded that learning using Hawgent Dynamic software could help in mathematics. It was easier and satisfying for students to understand the material about building a curved side space. However, the use of Hawgent software was only limited to trials, so it was recommended that it be able to use and utilize this software for other discussions on mathematics lessons.